ANALISIS FAKTOR FAKTOR PENYEBEBAB RENDAHNYA MINAT BACA SISWA DAN SOLUSI YANG ADA DI SEKOLAH DASAR NEGERI 4 BANJAR: Rendahnya Minat Baca - Risma Damayani; Luh Putu Sri Ariyani; I Putu Putra Yana Wardana (ACARYA PUSTAKA, 2026)
This study aims to examine the factors contributing to the low reading interest among students and to identify strategic solutions that can be applied at SD Negeri 4 Banjar. The lack of reading interest among elementary school students has an impact on their literacy skills and academic achievement. This research employs a qualitative approach with a descriptive method. Data were collected through field observations, interviews with students, teachers, and the school principal, as well as document analysis. The findings indicate that the main factors causing low reading interest include the limited availability of engaging reading materials, insufficient encouragement from teachers and parents, students’ lack of awareness of the importance of reading, and the excessive use of gadgets. Moreover, the school library has not been optimally utilized to support literacy activities. Recommended efforts include strengthening literacy programs such as a 15-minute reading activity before lessons, providing a wider variety of age-appropriate books, training teachers in literacy-based learning, and fostering collaboration between schools, librarians, and parents to cultivate a reading culture. The results of this study are expected to serve as a reference for other elementary schools in developing effective strategies to enhance students’ reading interest from an early age.